KAJIAN HUKUM PEMEGANG IZIN USAHA PEMANFAATAN HASIL HUTAN KAYU HUTAN ALAM (IUPHHK-HA) TERHADAP PENERAPAN KEBIJAKAN KEMENTRIAN LINGKUNGAN HIDUP KEHUTANAN NO.P.30/MENLHK/SETJEN/PHPL.3/3/2016 TENTANG PENILAIAN KINERJA PENGELOLAAN HUTAN PRODUKSI LESTARI DAN VERIFIKASI LEGALITAS KAYU PADA PEMEGANG IZIN, HAK PENGELOLAAN ATAU PADA HUTAN HAK - Ilham Hadiansyah (Universitas 17 Agustus 1945 Samarinda, 2019)
ABSTRACT Sustainable Production Forest Management is an activity in the management of forests with the principle of protecting the forest to remain continue to be sustainable. So that forests in the future will still exist with good and sustainable management in accordance with the Regulation of the Minister of Environment and Forestry with compliance with the regulations contained therein. The method used in this study uses normative juridical research methods. Based on research results, Sustainable Production Forest Management arises from the existence of illegal logging and Forests as the world's lungs, with the Minister of Environment and Forestry Regulation No. P.30 / MenLHK / Setjen / 3/3/2016 concerning Performance Assessment of Sustainable Production Forest Management and Timber Legality Verification on Permit Holders, Management Rights or on Private Forests. In order to the forests in Indonesia in particular are always preserved. Keywords: Obligations of Permit Holders to Implement SustainableProduction Forest Management.